Buru Language Learning Management Model in Ecotourism-Based Embedded-Multilingual: Teachers’ Need Analysis - Tahir, Saidna Zulfiqar Bin; Sakkir, Geminastiti; Iye, Risman (Idarah (Jurnal Pendidikan dan Kependidikan), 2024)
11 of the 71 regional languages have been declared extinct, most of which come from Maluku, North Maluku, and Papua. To prevent the extinction of several regional languages in Maluku, thus, this research aims to design an integrated model of Buru language learning based on Embedded Multilingual Ecotourism. While the specific objectives are to investigate the needs analysis of elementary school teachers for Buru language learning in the Embedded multilingual model, to explore what methods teachers use in teaching Indonesian and English using the Buru language, and to design learning textbook materials. Buru language in ecotourism-based embedded multilingual learning effectively preserves the local language for students of 9 Elementary Schools in Buru Regency. To support the achievement of the objectives of this study, the researcher used the R&D research model developed by Borg & Gall. The steps of R&D research are in the form of a cycle, which includes reviewing research findings, developing products based on these findings, testing in the field with settings according to where this product will be applied, and revising it based on the results of field tests. This process continues to be repeated until the developed product meets the stated objectives. The study results found the need for primary school teachers in Buru Regency to design ecotourism-based learning models and multilingual textbooks that contribute to teaching the Buru local language and prevent it from extinction.